2007
DOI: 10.1158/1078-0432.ccr-07-1119
|View full text |Cite
|
Sign up to set email alerts
|

In vivoDiagnosis of Epidermal Growth Factor Receptor Expression using Molecular Imaging with a Cocktail of Optically Labeled Monoclonal Antibodies

Abstract: Purpose: Epidermal growth factor receptors (EGFR) play an important role in tumorigenesis and, therefore, have become targets for new molecular therapies. Here, we use a “cocktail” of optically labeled monoclonal antibodies directed against EGFR-1 (HER1) and EGFR-2 (HER2) to distinguish tumors by their cell surface expression profiles. Experimental Design: In vivo imaging experiments were done in tumor-bearing mice following s.c. injection of A431 (overexpressing HER1), NIH3T3/HER2+ (overexpress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 20 publications
5
92
0
Order By: Relevance
“…Pharmacokinetics of trastuzumab conjugate was consistent with previous findings by other groups using different fluorophores, thus verifying our imaging system (43,44). On the contrary, Affibody monomer Z HER2:342 -Alexa Fluor 750 conjugate failed to show clear signs of tumor accumulation and fast clearance.…”
Section: Conjugatessupporting
confidence: 91%
“…Pharmacokinetics of trastuzumab conjugate was consistent with previous findings by other groups using different fluorophores, thus verifying our imaging system (43,44). On the contrary, Affibody monomer Z HER2:342 -Alexa Fluor 750 conjugate failed to show clear signs of tumor accumulation and fast clearance.…”
Section: Conjugatessupporting
confidence: 91%
“…Examples include the small molecule 2-deoxyglucose (2-DG), 23,24 small peptide RGD, 25 large peptides annexin V, 26 EGF, 5,6,27,28 affibody, 15,29 and large antibodies. [30][31][32] Quenched probes that only produce fluorescence signals in the presence of tumor-specific proteinases have also been developed. 33 Cell surface receptors, such as EGFR, that are overexpressed in cancers can be reliable targets for molecular imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Coincident administration of different coloured probes that target several cell surface determinants can further facilitate tissue discrimination. Pre-clinical studies [35][36][37] have shown that cocktails of antibodies labelled with differently coloured fluorescent tags could differentiate between different tumour types. Thus, Longmire et al [35] recently demonstrated that the use of conjugates consisting of trastuzumab-rhodamine green to target HER-2 could discriminate HER-2-overexpressing cells from SHIN3-RFP (red fluorescent protein) tumour cells, which are engineered to express red fluorescence.…”
Section: Optical Probesmentioning
confidence: 99%
“…Thus, Longmire et al [35] recently demonstrated that the use of conjugates consisting of trastuzumab-rhodamine green to target HER-2 could discriminate HER-2-overexpressing cells from SHIN3-RFP (red fluorescent protein) tumour cells, which are engineered to express red fluorescence. Barrett et al [36] were able to detect and differentiate tumours overexpressing HER-1 and HER-2 24 h after administration of a mixture of Cy5.5-labelled cetuximab and Cy7-labelld trastuzumab. Koyama [37] used multifilter spectrally resolved optical imaging to detect tumours overexpressing HER-1, HER-2 and interleukin-2 receptor alpha-subunit receptor (IL-2Ra) grown as xenografts using cetuximab-Cy5 (targeting HER-1), trastuzumab-Cy7 (HER-2), and daclizumab-Alexa-Fluor-700 (IL-2Ra) labelled antibodies, respectively, in mice.…”
Section: Optical Probesmentioning
confidence: 99%